ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Annisaa, Annisaa Ramadhanty (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to analyze the financial performance of Regency/City Governments in South Sumatra Province as measured by comparative analysis of financial statements, analysis of percentage per component, analysis of sources and use of funds, trend analysis and ratio analysis. The data used in this study is secondary data in the form of Budget Realization Reports (LRA), Operational Reports (LO) and Balance Sheets of 17 Regency/City Governments in South Sumatra Province in 2016-2020, obtained from the documentation of the Supreme Audit Agency of the Republic of Indonesia (BPK RI). The data analysis technique uses financial ratio analysis. The results of the study show that the financial performance of the Regency/City Government in South Sumatra Province during 2016-2020, among others: (1) The regional financial independence ratio shows that the results are not yet independent, (2) the PAD effectiveness ratio during 2016-2020 averages less. effective, (3) the average expenditure efficiency ratio shows very inefficient, (4) the ratio of activities owned by the regional government is still prioritized for operating expenditure needs so that the allocation of capital expenditure is relatively smaller, (5) the ratio of income growth fluctuates from year to year. year.